A curious case of asymptomatic septic knee in closed tibial plateau fracture - Ayeop, Mohd Adham Shah; Siron @ Baharom, Khairul Nizam; Zayzan, Khairul Rizal; Sharifudin, Mohd Ariff; A., Nur Shida; Zulkifly, Ahmad Hafiz (2014)
Tibial plateau fracture is a common injury following high velocity trauma. A closed tibial plateau fracture is treated with internal fixation. There is no incidence of a septic knee being reported following a closed tibial plateau fracture. The following report highlights a case of closed tibial plateau fracture with an incidental finding of intraarticular pus collection.